The Influence of Service Quality and Price on Customer Satisfaction of Grab Bike Features in Bandung City - Moh. Aep Nurjamad; Siti Zalikho (International Journal of Integrative Sciences, 2023)
The subjects of this study were the citizens of Bandung. The goal of this study was to ascertain how much, either partially or concurrently, service quality and pricing had an impact on customer satisfaction for the Grab Bike feature in Bandung City. Descriptive and associative research methods were employed in this study. Individuals, specifically consumers who download the Grab application and use the Grab Bike service feature in the city of Bandung, serve as the unit of analysis in this study. Purposive sampling with non-probability is the sampling approach employed in this study. Due to the uncertainty surrounding the population size, the researchers employed the Lemeshow technique to generate a total of 96 samples. Ways for gathering data via a questionnaire. Multiple linear regression analysis is used in the analytical process, and the research instrument is also subjected to validity and reliability testing. Based on the study's findings, it can be concluded that the independent variables (service quality and price) have a partial or simultaneous positive influence on the dependent variable (consumer satisfaction)